THE EFFECT OF BLOWN AND WORK EXPERIENCE OF PROFESSIONAL NURSING MODEL (MAKP) THROUGH NURSING COMPETENCE IN SAYANG HOSPITAL THE PEOPLE MAKASSAR - Mattalatta, Mattalatta; Kadir, Ikhsan; Fitriani, Eva (YUME : Journal of Management, 2020)
This study aims to test and analyze the influence of training and work experience on the professional nursing care model (MAKP) through nurse competence at the Sayang Rakyat Hospital Makassar. The research design used in this study was a survey with a quantitative approach. The study population was all nurses in the RSUD Sayang Rakyat Makassar. The method of determining the sample used in this study uses a total sampling technique (saturated sampling) with a total sample used by 100 respondents. Data analysis using path analysis using multiple linear regression test.The results showed that: Training for nurses' competencies in the RSUD Sayang Rakyat Makassar had a positive and significant effect with a significance value obtained of 0.006 <0.05. Work experience on nurses' competencies in the RSUD Sayang Rakyat Makassar has a positive and significant effect with a significance value obtained of 0,000 <0.05. Nurse competence towards MAKP in Sayang Rakyat Makassar Hospital has a positive and significant effect with a significance value obtained of 0,000 <0.05. Training on MAKP at the RSUD Sayang Rakyat Makassar has a positive and significant effect with a significance value obtained of 0.027 <0.05. Work experience on MAKP in the RSUD Sayang Rakyat Makassar has a positive and significant effect with a significance value obtained of 0,000 <0.05. Training for MAKP through nurse competence in the RSUD Sayang Rakyat Makassar has a positive and significant effect with tcount <ttable or 1,636 <1,660. Work experience on MAKP through nurse competence in the RSUD Sayang Rakyat Makassar has a positive and significant effect with tcount> ttable or 1,933> 1,660.Keywords: Education and Training, Work Experience, Nurse Competence, Professional Nursing Care Model (MAKP)